1997
DOI: 10.1002/clc.4960200412
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrite/nitrate level is inversely correlated with plasma low‐density lipoprotein cholesterol level

Abstract: SummaryBackground: Plasma nitritehitrate (NOx) is a stable end product of the vasodilator nitric oxide (NO). However, there are few reports about plasma NOx levels in humans.Hypotlzrsis: The purpose of this study was to assess the availability of plasma NOx for evaluating basal endogenously-synthesized or endothelium-derived NO, and to examine whether NOx levels are lowered in patients with coronary artery disease (CAD) or its risk factors.Metlzods: Plasma NOx levels were measured using an automated system bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 21 publications
4
29
1
Order By: Relevance
“…They also found temporal variability in NOx levels, which were most reproducible and lowest at 0600 [64]. This confirmed the work of Nakashima, who found that treatment of hypercholesterolemic adults with the cholesterol lowering agent, Simvastatin, increases plasma NOx (from 8 ± 17 µmol/l to 57 ± 32 µmol/l), within 12 weeks, in a manner that correlated with the rise in high density lipoprotein [65].…”
Section: Normal Values For Noxsupporting
confidence: 81%
See 1 more Smart Citation
“…They also found temporal variability in NOx levels, which were most reproducible and lowest at 0600 [64]. This confirmed the work of Nakashima, who found that treatment of hypercholesterolemic adults with the cholesterol lowering agent, Simvastatin, increases plasma NOx (from 8 ± 17 µmol/l to 57 ± 32 µmol/l), within 12 weeks, in a manner that correlated with the rise in high density lipoprotein [65].…”
Section: Normal Values For Noxsupporting
confidence: 81%
“…Tanaka et al reported normal plasma NOx values of 4.9±2.3 × 10 -5 M (49 µmol/l) [64] and also noted that NOx levels were lower for patients with hypercholesterolemia. They also found temporal variability in NOx levels, which were most reproducible and lowest at 0600 [64].…”
Section: Normal Values For Noxmentioning
confidence: 96%
“…Besides the present study, we also previously demonstrated that long-term treatment with simvastatin, a HMG-CoA reductase inhibitor, significantly enhances plasma NOx concentration in patients with hypercholesterolemia (16) and that plasma NOx level is inversely correlated with plasma level of lowdensity lipoprotein cholesterol in humans (24). However, whether NOx is a reliable marker of NO formation in vivo is still controversial, and indeed there are conflicting facts regarding plasma NOx level in hypertensive individuals: two studies reported that plasma NOx concentrations were significantly reduced in patients with essential hypertension compared to those in normotensive healthy subjects (12,25) whereas one study showed that plasma NOx levels were similar in refractory hypertensive patients and normotensive healthy subjects (26).…”
Section: Nox As a Marker Of No Formation In Vivosupporting
confidence: 80%
“…Some reports have noted that there was an increased NOx level in coronary artery disease (CAD) in patients with abnormal lipid profiles, 25) while another study reported that the NOx level was not related to the disease and the level decreased only in hypercholesteremic patients with CAD. 26) The inhibitory effects of ASX against lipid peroxidation and lipoprotein oxidation have been mentioned in a number of studies. 27,28) In this experiment, the effect of ASX-O on lipid peroxidation was not significant compared to the olive oil control, which also showed a similar effect.…”
Section: Discussionmentioning
confidence: 99%